2011
DOI: 10.1177/0887403410390510
|View full text |Cite
|
Sign up to set email alerts
|

Off-Duty and Under Arrest

Abstract: The findings of independent commissions and research derived from a data set of career-ending misconduct among New York Police Department (NYPD) officers suggests that police engage in a wide variety of crimes while they are off duty including domestic violence, bar fights, drunk driving, burglary, and sex offenses (Fyfe & Kane, 2006; Kane & White, 2009; Mollen Commission, 1994). The off-duty misbehavior of police is an important concern for police agencies exposed to potential liability costs, and sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
0
22
1
Order By: Relevance
“…In general, studies show some police officers commit a variety of misdemeanor and felony offenses (Fyfe & Kane, 2006;Harris, 2010;Stinson et al, 2012). Police crime occurs in small and large law enforcement agencies located in every state throughout the USA, both on-and off-duty (Stinson et al, 2012). Early studies of police crime revealed some officers commit on-duty criminal activity, including the acceptance of bribes and petty theft (e.g.…”
Section: The Nature Of Police Crimementioning
confidence: 97%
See 3 more Smart Citations
“…In general, studies show some police officers commit a variety of misdemeanor and felony offenses (Fyfe & Kane, 2006;Harris, 2010;Stinson et al, 2012). Police crime occurs in small and large law enforcement agencies located in every state throughout the USA, both on-and off-duty (Stinson et al, 2012). Early studies of police crime revealed some officers commit on-duty criminal activity, including the acceptance of bribes and petty theft (e.g.…”
Section: The Nature Of Police Crimementioning
confidence: 97%
“…Officers who are arrested for crimes committed both on-and off-duty are more likely than other officers who are arrested to receive a suspension as a final adverse employment outcome. Likewise, arrests for on-duty crimes are more likely to result in an arrested officer's resignation, and arrests of officers for off-duty crimes are more likely to result in the termination of the officers' employment (Stinson et al, 2012).…”
Section: The Nature Of Police Crimementioning
confidence: 97%
See 2 more Smart Citations
“…Police officers do not like to arrest other officers, and often minor transgressions are ignored whereas similarly situated nonpolice citizens would be arrested for their crimes (Black, 1976). The off-duty crimes for which officers are sometimes arrested include domestic violence and other assaults, driving under the influence (DUI), and various sex crimes (Stinson, Liederbach, Brewer, & Todak, 2013;Stinson, Liederbach, & Freiburger, 2012;). …”
Section: The Current Studymentioning
confidence: 99%